Partnerships for Better Education Results - World Bank (World Bank, Washington, DC, 2017)
The World Bank Group’s Systems Approach for Better Education Results (SABER) initiative produces data on education system policies and institutions, analyzes and evaluates their quality, and provides decision makers and stakeholders with an assessment that fosters structured and informed policy dialogue on how to most effectively strengthen education systems. During its tenure, SABER has grown rapidly to become a key component in the design of education programming across the globe, providing countries with quality data and information. By generating a broader knowledge base on education systems worldwide, these tools are helping reform education at the country level while also building a high-quality knowledge base for education reforms at the global level. As SABER has evolved and gained traction globally, international development institutions, regional organizations, and national and local governments have partnered with SABER domain teams and adapted SABER tools for more effective engagements.